Tilt Observations at the Seafloor by Mobile Ocean Bottom Seismometers - Shiobara, Hajime; Ito, Aki; Sugioka, Hiroko; Shinohara, Masanao; Sato, Toshinori (Frontiers in Earth Science, 2021)
We have developed a broadband ocean bottom seismometer (BBOBS) and its new generation (BBOBS-NX) with the penetrator sensor system since 1999. With them, we performed many practical observations to create a new research category of ocean bottom broadband seismology. As the next step in seafloor geophysical observation, the BBOBS and the BBOBS-NX can be a breakthrough in realizing a geodetic observation network on the seafloor. Although vertical displacement observation by the absolute pressure gauge has been widely conducted in recent years, other geodetic observations are rarely performed. A few trials to measure the seafloor tilt were performed, but those looked inadequate for practical observations. Note that the broadband sensor in our BBOBSs has a mass position signal output, which can be used to measure the tilt change. As the horizontal component noise level of the BBOBS-NX is good at a long period range, we expected it to be adequate for the tilt measurement. At the first evaluation, we performed a comparison with a water-tube tiltmeter. The result was comparable with a resolution of better than 1 µ radian. A practical observation at the south of Boso Peninsula (KAP3 site) was conducted as the in-situ study from April, 2013. In January, 2014, a slow slip event (SSE) occurred near this site. The tilt data were processed by removing steps, mechanical relaxation, and tides. The results show a clear peak started from late December 2013. Two more 2 year-long tilt observations began in 2015: one was at the KAP3 site and another was off the Miyagi Prefecture at the slope to the Japan Trench. The latter was recovered in 2017 with about 1.5 years of data, which indicate a large continuous tilt up to several tens of µ radian. This amount of tilt can be explained by a similar already estimated SSE. Mobile tilt measurement at the seafloor can be a powerful tool to study SSEs, as they can be located above the source area and also possible to build an observation array for a practical study because of its low cost and ease of deployment compared with a seafloor borehole site.